Allusion and Their Level in the Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses some of the specific features of the artistic language of women's poetry. It discusses anthroponyms used in women's poetry, and discusses the linguopoetic function of lexemes that are literary pseudonyms, talmeh, and allusions. Attention is paid to how the aforementioned poetic devices play a role in women's poetry and what similarities and differences they have with these methods, which are also artistic devices in men's poetry. In this process, it is shown that anthroponyms create allusions, are mainly used in the artistic reflection of the authors' worldview and state of mind, and in some places serve to reveal the spiritual experiences of traditional characters against the backdrop of emotionality.